A retrospective analysis of the impact of a hospital pharmacist-led procalcitonin protocol. (9th November 2021) - Cowey, Carrolyn K; Wilson, Erica
Abstract: Purpose: Procalcitonin is a precursor hormone to calcitonin that increases in response to systemic inflammation, especially of bacterial origin, and is otherwise undetectable in healthy states. Studies have shown that following effective antimicrobial treatment, procalcitonin levels steadily decline. To be utilized however, procalcitonin levels determinations must be ordered at specific times during a patient's antimicrobial treatment. A retrospective medication-use evaluation of patients was performed at Medical Center Hospital and showed that in 70% of patients, initial procalcitonin levels were ordered inappropriately and procalcitonin levels were trended inconsistently during antibiotic treatment. Methods: A pharmacist-led procalcitonin protocol was developed and presented to medical staff committees for approval. Data was collected from patients presenting with suspected or confirmed sepsis or lower respiratory tract infections for whom procalcitonin levels were utilized. Patient outcomes before and after protocol implementation were compared. Results: A total of 400 patients were included in the study. The primary outcome of appropriate ordering of initial procalcitonin levels was improved in the postprotocol group relative to the preprotocol group (28% of patients [ n = 56] vs 72% of patients [ n = 144]; P < 0.001). Patients in the postprotocol group had a procalcitonin level checked at discontinuation more frequently (8% [ n = 16] vs 37% [ n = 74], P < 0.001) and had a higher rate of appropriate discontinuation of antibiotics (12% [ n = 21] vs 46% [n = 77]; P < 0.001). The postprotocol group also had fewer mean days of antibiotic therapy (9.17 vs 6.01; P < 0.001). Conclusion: Studies have shown the usefulness of procalcitonin levels for antimicrobial stewardship, but for procalcitonin testing to be properly utilized it must be ordered at the correct times during the patient's therapy. The implementation of a hospital-wide pharmacist-led protocol resulted in an increase in appropriate ordering of baseline procalcitonin levels.